THE ABILITY TO TRANSLATE ENGLISH PHRASES INTO INDONESIAN AND THE DIFFICULTIES FACED BY THE ELEVENTH GRADE STUDENTS OF SMAN 1 PANCARIJANG - Nadirah, Nadirah; Tahir, M. Hijaz; Asrifan, Andi (JOURNAL OF ADVANCED ENGLISH STUDIES, 2019)
The research aims at finding out the ability to translate English phrases into Indonesian which cover the noun phrase, verb phrase, adjective phrase, adverb phrase, and prepositional phrase; and also the difficulties faced by the eleventh-grade students of SMAN 1 Pancarijang. The research will employ the descriptive method. It will take six classes, and each class consisted of thirty-five students which mean that is 210 students as the population in this research. It will use a proportional random sampling technique to minimize the big population. The researcher will take 7 students randomly for each class, totally 42 students. The data will be collected by using a reading test, questionnaire and interview to know the students’ ability which will be analyzed through SPSS 21.0. The research result will be indicated that the translate English phrases into Indonesia can develop ability students’ of SMAN 1 Pancarijang. The research method employed was a descriptive method. The research data were collected using three kinds of the instrument which test to asses students’ ability to translate English phrases into Indonesian, questionnaire, and interview to know the difficulties faced in translating English phrases into Indonesian was analyzed descriptive method. The findings of the research showed that the students’ mean score in translation test is 78.43 and it was categorized as good. The study concluded that (1) the students have a good ability in translating English phrases into Indonesian, and (2) although the students have good ability in translating English phrases into Indonesian, they still face difficulties in translation. Most of the difficulties dealt with the ‘language problem’ which is related to vocabulary and structure. It is more vocabulary and grammar in order to minimize the difficulties faced by students in translation. It is then recommended for further related research to conduct research on other types of translation test.